Mobile banking acceptance among young consumers in Germany : an empirical analysis - Rilling, Steffen Nicholas Konstantin (2015)
Purpose: While Germany leads the adoption of internet banking with only a few nations beforehand, in terms of mobile banking (MB), the country encounters difficulties. Major banks in Germany spend large budgets on refined MB services. Nonetheless, the share of MB customers is only at approximately 10%. It appears crucial for MB service providers to develop a deeper understanding of MB acceptance, especially among young customers that are usually considered as early adopters of technology. In consequence, this dissertation aims at identifying key MB acceptance factors for young customers in Germany. Design/Methodology/Approach: Founded on the Unified Theory of Acceptance and Use of Technology (UTAUT), this study develops a research model specifically tailored to the context of MB. Following, it examines 433 young consumers in Germany and applies Structural Equation Modelling (SEM) in order to test the network of hypotheses in the proposed model. Subsequently, a multi-group analysis inspects differences between users and non-users of MB. Findings: The results indicate strong evidence for the validity of the proposed research model, which explains 67.7% of variance regarding behavioural intention to adopt MB. The study suggests that Perceived Compatibility has the strongest effect on Behavioural Intention. Perceived Credibility, Performance Expectancy, Effort Expectancy, and Social Influence, ordered by their effect size, significantly influence Attitude towards MB, which in turn influences Behavioural Intention. Originality/Value: The results have several implications for scholars and practitioners. While scholars receive new empirical support for theory development, practitioners gain a deeper understanding of the key adoption factors to design and implement new MB concepts that yield high consumer acceptance.